(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Natural Products from medicinal plants either as pure or as a standardized extracts provide unlimited opportunities for new drugs because of the unmatched availability of chemical constituents. Since ancient times, natural products have been utilized to treat and cure chronic diseases like cancer, diabetes, asthma, anti-inflammatory, analgesic and as alternatives for hormone replacement therapy worldwide. According to the World Health Organization (WHO), more than 80% of the world's population relies on traditional medicine for their primary healthcare needs. Despite their widespread existence, the variety of bioactive natural products in natural medicines are not sufficient. Today, it is very crucial to develop effective and selective methods for the extraction and isolation of new natural products. The focus of this review paper is to provide a comprehensive view on the analytical methodologies, which include extraction, isolation and characterization of the natural products from medicinal plants and common phytochemical screening assays.